Malaysia and South China Sea policy, strategy and risks - B.A Hamzah; Leong, Adam; Forbes, Vivian (Centre for Defence and International Security Studies (CDISS), NDUM, 2020)
This volumes features a series of eight chapters presented by ten contributors who offer narratives to explain the policy, diplomatic and military strategies and associated risks relating to Malaysia's actual and potential actions in dealing with the territorial and sovereignty issues in the South China Sea.